Predictors of mortality among COVID-19 patients - A case control study at tertiary care center, Nanded (Maharashtra) - Prakash L Gattani; Mahavir P Nakel; Ismail F Inamdar; Sainath L Maidapwad; Omprasad B Damkondwar; Komal S Warkad; Rajabhau S Butte; Abhijeet L Bansode (Wolters Kluwer Medknow Publications, 2023)
Background: The novel Coronavirus is belonging to the family of SARS & MERS-CoV, the impact of the earlier is more dreadful as demonstrated by the steady increase in morbid cases. The average incubation period of COVID-19 is 1-14 days with a mean of 6 days. Aim - To evaluate predictors of mortality among COVID-19 patients. Objectives - 1. To assess risk predictors associated with mortality among COVID-19 patients 2. To a suggest prediction model for preventing mortality in future outbreaks. Materials and Methods: Study design - A case-control study. Study place -Tertiary care center, Nanded, Maharashtra. The present study included 400 cases that died off due to Covid-19 and 400 controls survived COVID-19 disease in a 1:1 proportion. Results: On admission, a significant difference was observed among cases and controls with reference to the percentage of SpO2 (p < 0.05). The proportion of associated co-morbidities among cases was very high i.e., 75.75% as compared to controls with a proportion of 29.25% co-morbidities. The median days of hospital stay were significantly lower in cases compared to controls (3 days vs 12 days, P < 0.001). Conclusion: Length of hospital stay (in days) was showing a significant difference among cases and control (3 days Vs 12 days); hospital stay was less (median 3 days) for cases, as they reported late and thus died earlier; hence concluded that early hospital admission will decrease chances of death due to COVID-19.